1984
DOI: 10.1111/j.1471-4159.1984.tb02764.x
|View full text |Cite
|
Sign up to set email alerts
|

Proton Nuclear Magnetic Resonance Spectroscopy of Rabbit Brain Homogenate

Abstract: Proton nuclear magnetic resonance (1H NMR) spectroscopy in conjunction with the inversion-recovery spin-echo pulse sequence was used to obtain spectra from rabbit brain homogenate. The instrumental parameters required for the acquisition of spectra together with the assignment of major peaks are given. The rationale and prospectus for the use of this technique for the study of neurochemistry is outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Later work suggested that other brain constituents having N-acetyl moieties (e.g., N-acetylaspartylglutamate), also contribute to signal intensity in this region of the spectrum (5,6). Published evidence also shows that glutamate, glutamine, and various macromolecular constituents contribute to this spectral region (4,(7)(8)(9)(10)(11)(12), although it is unlikely that these latter signals are present in long echo time spectra, of the sort we present here, due to T, and J-modulation losses (12). Despite the controversy, most investigators accept the notion that NAA is a major contributor to the 2.02 ppm signal.…”
Section: Introductionmentioning
confidence: 51%
“…Later work suggested that other brain constituents having N-acetyl moieties (e.g., N-acetylaspartylglutamate), also contribute to signal intensity in this region of the spectrum (5,6). Published evidence also shows that glutamate, glutamine, and various macromolecular constituents contribute to this spectral region (4,(7)(8)(9)(10)(11)(12), although it is unlikely that these latter signals are present in long echo time spectra, of the sort we present here, due to T, and J-modulation losses (12). Despite the controversy, most investigators accept the notion that NAA is a major contributor to the 2.02 ppm signal.…”
Section: Introductionmentioning
confidence: 51%